PENGARUH KOMUNIKASI, KOMITMEN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI THE HAVEN BALI SEMINYAK - Ni Made Ina Pratiwi; A.A. Ketut Sri Asih; I Putu Agus Suarsana Ariesta (Journal Research of Management, 2026)
An employee's performance is a reflection of both their actions and the results they produce while on the job.  The purpose of this research is to identify the most important factor affecting employee performance at The Haven Bali Seminyak by analysing the relationships between communication, job dedication, and the work environment.  A quantitative strategy is used in the research. A saturation sampling technique is used to collect data from 95 respondents using a five-point Likert scale questionnaire.  Statistical methods such as multiple linear regression, hypothesis testing, classical assumption tests, and descriptive statistics were used to analyse the data.  Employee performance is positively and significantly impacted by work environment, job dedication, and communication, with communication being the most influential of these three factors.  Effective communication is crucial for boosting employee performance, and the findings highlight this importance, which contributes to better management practices.